Assembly Sequence Optimization based on Improved Genetic Algorithm - Yang Wei; Meng Guanjun; Cao Wengang; Xie Kunfeng; Yu Pengfei (Jixie chuandong)
According to the assembly sequence optimization problem of mechanical products,the assembly sequence is used as initial population,and the reference set is added to the genetic algorithm,and the intelligent iterative mechanism of the decentralized search algorithm is used to avoid the random nature of the search.The continuous optimization of the assembly,the optimal solution is obtained. Finally,the effectiveness and feasibility of the improved genetic algorithm is verified through the analysis of the three stage reducer.